The Role of Organizational Culture in The Relationship Between Workforce Diversity and Employee Performance of Generation Y - Melinda, Melinda; Nuraini, Endah (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2024)
Workforce diversity is a common problem among employees. However, according to Forbes, the application and literature on this topic still need to be improved, even though it is considered a major issue. This research aims to determine the role of organizational culture in the relationship between employee diversity and employee performance, focusing on the Indonesian Y generation who have worked on the island of Java for at least one year. A total sample of 345 Generation Y workers on Java Island was used, and PROCESS MACRO by Hayes was used to determine the role of organizational culture. The research results show that workforce diversity significantly and positively affects organizational culture. Organizational culture has a significant and positive effect on employee performance. Workforce diversity has a significant and positive effect on employee performance. In addition, it was found that organizational culture does not act as a moderator but rather acts as a mediator in the relationship between workforce diversity and employee performance. This role was found to be a mediator after further analysis was carried out. It is highly recommended that future researchers use a more significant number of samples and islands other than Java or choose certain industries to enrich research results. Additionally, the use of other diversity attributes may contribute to the diversity of results.